Skills to shape the future: Employability in Belize - Näslund-Hadley, Emma; Navarro-Palau, Patricia; Fernanda Prada, María (Inter-American Development Bank, Social Sector Department, Education Division, 2020)
This study yields new insights on the changing landscape of Belize’s economy and the challenges of equipping students and workers with the skills they need to thrive in an evolving labor market. Using census and labor force data, we show that Belize’s economy is transitioning toward services and away from agriculture, manufacturing, and construction. We find that the country has potential for workforce development in a range of soft and digital skills that are in high demand in various sectors. We also show that women constitute an untapped resource for economic growth, especially given Belize’s growing need for an educated workforce and women’s higher education attainment. Using a survey of employers and training institutions, we document a skills mismatch between employers’ needs and workers’ skills. Finally, we propose five principles that could guide education and employment policies to help close the skills gap.
Keywords: equipping students; labor market; workforce development; higher education; skills; employability; skills mismatch; STEM